2007
DOI: 10.1590/s0074-02762007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Slime production and antibiotic susceptibility in staphylococci isolated from clinical samples

Abstract: Slime production is considered to be a significant virulence factor for some strains of staphylococci (Christensen et al. 1982, Davenport et al. 1986, Kleeman et al. 1993, Ammendolia et al. 1999, Mack et al. 2000. In coagulase-negative staphylococci (CNS), a loosely bound exopolysaccharides layer (slime) has been found in addition to capsule, and it has been associated with sepsis, including intravenous-catheter-related bacteremia and other prosthetic device infections (Ishak et al. 1985, Diaz-Mitoma et al. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
19
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
(26 reference statements)
9
19
0
3
Order By: Relevance
“…The results of our study are similar to previous literature, in which the percentage of slime-producing strains of S. epidermidis ranged from 31% to 89% [20,21]. In addition, we found a statistical difference with regards to slime production between the clinical isolates from the patient catheter blood specimens and isolates from the nasal vestibules of three groups (p<0.05) (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The results of our study are similar to previous literature, in which the percentage of slime-producing strains of S. epidermidis ranged from 31% to 89% [20,21]. In addition, we found a statistical difference with regards to slime production between the clinical isolates from the patient catheter blood specimens and isolates from the nasal vestibules of three groups (p<0.05) (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…The data reported here indicate an important role of slime production as a virulence marker for S. epidermidis, where 83.3% of the isolated S. epidermidis were slime producer. These results similar to those reported by [37] who found that clinical CoNS isolates had a high frequency of slime production and drug resistance, particularly S. epidermidis strains.…”
Section: Discussionsupporting
confidence: 91%
“…The different colonization pattern may still have clinical relevance as mucosal colonisation is a potential source of CoNS in invasive infections [14]. Differences in the pathogenicity of CoNS species have been demonstrated with 71% of S. epidermidis but only 35% of S. haemolyticus and 26% of S. hominis strains being capable of slime production, the latter being associated with invasive disease [39][40][41]. The relevance of differences in gut colonization observed in this study is further supported by the clinical findings showing a trend towards greater prevalence of LOS caused by S. epidermidis in the penicillin compared with the ampicillin arm (7.6 vs 2.7 per 100 patient days, respectively).…”
Section: Discussionmentioning
confidence: 99%